(untitled) (Stamford Journal of Microbiology, 2017)
Sound microbiological quality of ice cream should be ensured for being a widely popular dairy food in the world. Present study was conducted to determine the microbiological quality of different ice cream samples available in Dhaka, Bangladesh. Total 3 ice cream samples were collected and processed to detect the microbiological quality as well as drug resistant trait of the isolates through several conventional Kirby Bauer method. All the samples were found to be contaminated with the total viable bacteria and fungi within the range of 1.2×104 cfu/ml to 4.3×106 cfu/ml. The presence of E. coli, Staphylococcus aureus was also observed up to 104 cfu/ml. However, the fecal contamination was totally absent in all the samples. Antibiotic profile of two isolates was measured against 8 commonly used antibiotics and both E.coli and Staphylococcus aureus were found to be resistant against more than one antibiotics. Appropriate hygienic and storage condition should be maintained concerning the health safety of consumers. Stamford Journal of Microbiology, Vol.7(1) 2017: 33-35